Semaphorin 3A deficiency improves hypoxia-induced myocardial injury via resisting inflammation and cardiomyocytes apoptosis - Zhao, C; Liu, J; Zhang, M; Wu, Y (Cellular and Molecular Biology, 2016)
Ischemia/hypoxia leads to heart injuries by inducing inflammation, cardiac fibrosis and cardiomyocyte apoptosis. Semaphorin 3A (Sema 3A) plays a regulatory role during all immune response stages, and has been demonstrated to be associated with multiple diseases. However, roles of Sema 3A during myocardial ischemia/hypoxia have not been studied in full. In this study, decline in Sema 3A was discovered in hypoxia-treated myocardial cells. When this decline was enhanced by silencing of Sema 3A gene, hypoxia-induced myocardial cell injury could be partially improved. Sema 3A deficiency can resist hypoxia-induced inflammatory factors (TNF-Î±, IL-1Î² and IL-6) secretion, cell viability decline, cardiomyocyte apoptosis, ROS release, ATP generation decline as well as GSH/GSSG ratio decline in H9C2 cells. Besides, hypoxia-induced bcl-2 decrease and cleaved caspase-3 increase also can be partially reversed during Sema 3A deficiency. All these findings reflect that reduced Sema 3A is a protective strategy adopted by damaged myocardial cell. Our study first shows that Sema 3A deficiency can improve hypoxia-induced myocardial cell injury, which thus offers a new insight to treatment ischemic heart disease.